Students Learning Anxiety in Maritime Vocational School - Hikmah, Nurul; Sukarno, Sukarno (Journal of Vocational Education Studies, 2025)
The objective of this study was to explore the levels of students’ anxiety, to reveal the factors influence students’ anxiety, and to reveal the students’ coping strategies for their anxiety in maritime English. This study was conducted using a mixed method. The participants consisted of 28 eleventh-grade students at SMK Pelayaran Nusantrara Barru, and a total of 23 students participating in the interviews. The researchers used a questionnaire to determine the students’ anxiety levels and interview to reveal the influencing factors and strategies to overcome their anxiety in maritime English. The findings showed that 23 out of 28 students experienced anxiety in maritime English. 16 students (57.14%) were in the mildly anxious level, 6 students (21.14%) were categorized as anxious level, 1 (3.57%) student fell into the very anxious level, 5 students (17.86%) were categorized as relaxed level, and none of them as very relaxed. The factors affected students’ anxiety in maritime English, including communication apprehension, test anxiety, fear of negative social evaluation, learning situations, assignments, teachers, maritime specific terms, and doubts of maritime English competence. In order to overcome anxiety, this study described that students used preparation; relaxation; positive thinking; focusing on the lessons; peer support practice, and students’ learning method as their strategies in the maritime English classes. As a conclusion, the majority of students were anxious in maritime English, caused by internal and external factors. Then, positive activities empirically impacted to solve anxiety during the maritime English learning.